Application of CRISPR/Cas9 technology in the modeling of Gaucher disorder - Mehran Reyhani-Ardabili; Mohadeseh Fathi; Soudeh Ghafouri-Fard (Biochemistry and Biophysics Reports)
Gaucher disease (GD) is a metabolic disorder caused by mutations in the GBA1, located on 1q22. This gene encodes glucocerebrosidase (glucosylceramidase) enzyme. GD has a wide range of clinical manifestations from a perinatally lethal type to an asymptomatic form. While different types of targeted therapies and hematopoietic stem cell transplantation have been suggested as therapeutic options for patients with GD, success rates were not optimal. Recent advance in the CRISPR technology has raised the hope for treatment of metabolic disorders such as GD. This technology has also facilitated identification of the molecular mechanisms underlying pathologic events in this disorder. The current review addresses both mentioned aspects of application of CRISPR technology in the field of GD.